Camphene as a Protective Agent in Myocardial Ischemia/Reperfusion Injury - Rodopi Stamatiou; Maria Anagnostopoulou; Konstantina Ioannidou-Kabouri; Chrysa Rapti; Antigone Lazou (MDPI AG, 2024)
Myocardial ischemia/reperfusion injury (I/R) and the resulting heart failure is one of the main causes of mortality and morbidity worldwide. Camphene has been shown to have anti-inflammatory and hypolipidemic properties; however, its role in the protection of the heart from ischemia and reperfusion has not been investigated. The cardioprotective role of camphene and the mechanism that mediates its action against I/R injury was evaluated in the present study. A single dose of camphene was administered in adult rats prior to ex vivo I/R induction. Infarct size was measured using 2,3,5-triphenyltetrazolium chloride (TTC) staining and cardiomyocyte injury was assessed by determining the release of the enzyme lactate dehydrogenase (LDH). Camphene pretreatment provided significant protection reducing myocardial infarct size and cell death after I/R. The effect was correlated with the reduction in oxidative stress as evidenced by the determination of protein carbonylation, GSH/GSSG ratio, the increase in mitochondrial content as determined by CS activity, and the modulation of antioxidant defense mechanisms (expression of Nrf2 and target genes and activities of CAT, MnSOD, and GR). Furthermore, ferroptosis was decreased, as demonstrated by downregulation of GPx4 expression and reduction in lipid peroxidation. The results suggest that camphene can protect the heart against I/R injury by maintaining redox homeostasis and can hold therapeutic potential for mitigating the detrimental effects of I/R in the heart.